PENERAPAN PRINSIP KESANTUNAN BERBAHASA PADA TUTURAN GANJAR PRANOWO DAN NAJWA SHIHAB DALAM ACARA MATA NAJWA - Elvira Putri Asri; Andiopenta Purba; Eddy Pahar Harahap (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the application of linguistic politeness principles in the utterances of Ganjar Pranowo and Najwa Shihab in the Mata Najwa program broadcast on the YouTube channel. Linguistic politeness is an important aspect of communication that reflects ethics and social norms in interaction. This research focuses on analyzing politeness maxims based on Geoffrey Leech’s theory, which includes the maxim of tact, the maxim of generosity, the maxim of approbation, the maxim of modesty, the maxim of agreement, and the maxim of sympathy. This study employs a qualitative descriptive method with a pragmatic approach. The data sources are the utterances spoken by Ganjar Pranowo and Najwa Shihab in episodes of the Mata Najwa program uploaded on YouTube. Data collection techniques were carried out using observation and note-taking methods, namely by watching the videos, transcribing the conversations, and recording utterances that contain principles of linguistic politeness. Data analysis was conducted by identifying, classifying, and describing the utterances based on politeness maxims, as well as analyzing compliance with and violations of linguistic politeness principles. The results show that the utterances of Ganjar Pranowo and Najwa Shihab reflect all six politeness maxims proposed by Leech. Both speakers tend to comply with politeness principles in communication, although several violations of politeness maxims were also found in certain contexts. Compliance with politeness maxims is demonstrated through the use of polite utterances, respect for interlocutors, and consideration of others’ feelings. Meanwhile, violations of politeness maxims occur in specific situations influenced by the conversational context, communication goals, and discourse strategies used in the talk show.